Urban Planning of Special Economic Zone Combined with Economic Structure - Han, Guangming; Zhu, Jing; Deng, Xiuqin (Open house international, 2016)
With the development of economy and the progress of science and technology, the function of Luoyang city is constantly enriched and expanded. The city is no longer a simple area for people to live in. The function structure of the city is affected by the external factors and is constantly expanding. Urban logistics is one of the important influencing factors. To more comprehensively and accurately understand the status and role of logistics network space in urban planning, the characteristics and development law of urban logistics structure from the theoretical point of view are analyzed in this paper with Luoyang City as the research background. The city logistics function is determined as one of the main factors affecting the economic growth of the city is determined through the literature search method, consulting professionals and other research methods. Urban road planning and design are the focus of the study; the planning and development of urban logistics road network in Luoyang City are compared and analyzed. In full consideration of the necessity of the optimization of the urban logistics network space, the preliminary optimization scheme design and suggestion of Luoyang logistics is introduced. At the end of this paper, the sustainable development and the status of the future urban logistics function are analyzed and prospected. Continuous research and analysis of multiple subjects and angles are still needed.